Diseño de una herramienta de cálculo para evaluar la confiabilidad metrológica del sistema térmico y gravimétrico del motor de combustión interna de la UAN-Sede Puerto Colombia (2020)
The main objective of this work is to design a calculation tool to evaluate the metrological reliability of the thermal and gravimetric system of the internal combustion engine of the UAN-Sede Puerto Colombia. The main motivation for the development of the project was the detected need to recover and place at the service of the student community of the UAN-Sede Puerto Colombia, the internal combustion engine of the experiment laboratory. In this sense, and considering the current problems related to COVID-19, this work aims to be a starting point to continue developing future projects aimed at motor recovery for academic activities, as well as those inherent in science, technology and the innovation. In specific terms, the project focused on a short experimental part where it was possible to design and implement a new PLC automation system for the combustion engine control system. A second part, which frames the contribution of the degree project, focused on the development of robust calculation tools that will allow, very easily, to know the errors and uncertainties associated with the system for measuring temperature and specific fuel consumption through the gravimetric method. In conclusion, it was found that the developed calculation tool was effective, once it was validated through the use of experimental data available in the specialized literature and it is available for subsequent projects within the same research area to be used.